Dialog Etika Kristen, Budaya Lokal, dan Transformasi Sosial: Integrasi Teologi dan Pendidikan Agama Kristen - Maxsi Tupamahu; Mey Linda Ubwarin; Florence Wineruru (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
The relationship between Christian ethics and local culture in the context of Indonesia’s multicultural society is a crucial issue in developing relevant and contextual Christian Religious Education (CRE). In practice, CRE has often been delivered in a normative and doctrinal manner, with limited integration of students’ cultural realities, resulting in weak internalization of faith values in daily life. This study aims to examine and formulate an integrative model of dialogue between Christian ethics and local culture from the perspective of contextual theology and its implications for CRE. This research employs a qualitative descriptive approach through library research, utilizing content analysis of relevant academic literature. The findings reveal that contextual theology provides a solid foundation for fostering a critical, reflective, and transformative dialogue between faith and culture. The integration of theological and pedagogical reflections through contextual, dialogical, and local wisdom-based approaches enhances students’ understanding of faith, character formation, and learning relevance. Furthermore, implementation models such as Contextual Teaching and Learning (CTL) contribute significantly to connecting Christian ethical values with students’ lived experiences. In conclusion, the dialogue between Christian ethics and local culture serves as a strategic approach in developing holistic, contextual, and transformative Christian Religious Education.